European tort law - Dam, C. C. van. (Oxford : Oxford University Press, 2013)
This textbook provides insight into the differences commonalities and mutual influece of the tort law systems of various European jurisdictions, bringing together national tort law, comparative law, EU law, and human rights law.
Previous ed.: 2006.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on Apr. 5, 2013).
Keywords: Torts -- Europe; Law; Laws of specific jurisdictions & specific areas of law